Prosodic skills in children with Down syndrome and in typically developing children. Issue 1 (30th June 2015) - Zampini, Laura; Fasolo, Mirco; Spinelli, Maria; Zanchi, Paola; Suttora, Chiara; Salerni, Nicoletta
Abstract: Background: Many studies have analysed language development in children with Down syndrome to understand better the nature of their linguistic delays and the reason why these delays, particularly those in the morphosyntactic area, seem greater than their cognitive impairment. However, the prosodic characteristics of language development in children with Down syndrome have been scarcely investigated. Aims: To analyse the prosodic skills of children with Down syndrome in the production of multi‐word utterances. Data on the prosodic skills of these children were compared with data on typically developing children matched on developmental age and vocabulary size. Between‐group differences and the relationships between prosodic and syntactic skills were investigated. Methods & Procedures: The participants were nine children with Down syndrome (who ranged in chronological age from 45 to 63 months and had a mean developmental age of 30 months) and 12 30‐month‐old typically developing children. The children in both groups had a vocabulary size of approximately 450 words. The children's spontaneous productions were recorded during observations of mother–child play sessions. Outcomes & Results: Data analyses showed that despite their morphosyntactic difficulties, children with Down syndrome were able to master some aspects of prosody in multi‐word utterances. They were able to produce single intonation multi‐word utterances on the same level as typically developing children. In addition, the intonation contour of their utterances was not negatively influenced by syntactic complexity, contrary to what occurred in typically developing children, although it has to be considered that the utterances produced by children with Down syndrome were less complex than those produced by children in the control group. However, children with Down syndrome appeared to be less able than typically developing children to use intonation to express the pragmatic interrogative function. Conclusions & Implications: The findings are discussed considering the effects of social experience on the utterance prosodic realization.